DIETARY EFFECT ON THE UTILIZATION OF CRUDE PROTEIN BY WHITE FULANI, FRIESIAN AND GERMAN BROWN CALVES FOR MAINTENANCE AND GROWTH - OGUNDOLA, F. I. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
Twenty-fourWhite Fulani, Friesian and German Brown male and female calves aged between one and eighty-four days were used in these studies. Each of the calves was assigned to one of the following treatment: